Comparison of Standardization of Ash Content of Butterfly Pea Simplicia (Clitoria ternatea L.): A Systematic Literature Review - Nurapni, Depita; Kamelia Risna; Kirana Azzahra Emil Musa; Riana Ardianti; Yeni Ari Safitri Dalimunthe (Eureka Herba Indonesia, 2023)
Butterfly pea flower (Clitoria ternatea L.) has been used extensively in traditional medicine due to its various health benefits. The ash content in the butterfly pea simplicia can provide important information about the mineral content and residues present in the material. This study aimed to carry out a systematic review in order to explore a comparison of the standardization of ash content of the butterfly pea flower simplicia. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding the comparison of standardization of ash content of Clitoria ternatea. This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. Several studies have shown variations in the ash content of butterfly pea flowers (Clitoria ternatea L.). The ash content of the butterfly pea flower (Clitoria ternatea L.) is in the range of 3.8 ± 0.42 mg/100 gram dry weight to 10.93 ± 0.29 mg/100 gram dry weight. Each plant has unique chemical characteristics, including different mineral content. Therefore, the ash content may vary between different plant species.